Isolation and identification of feruloylated arabinoxylan mono- and oligosaccharides from undigested and digested maize and wheat. Issue 5 (May 2016) - Malunga, Lovemore Nkhata; Beta, Trust
Abstract: Feruloylated arabinoxylan mono- and oligosaccharides (F-AXOS) are a subject of interest because of their prebiotic and antioxidant properties. We aimed at isolating and identifying F-AXOS from maize, wheat, wheat bran and wheat aleurone using HPLC and LC-MS/MS. Prior to extraction of F-AXOS, samples were subjected to either simulated gastric fluid with enzymes (gastric) or without enzymes (pH) or water (aqueous) at 37 °C. F-AXOS present in all samples were identified as 5-O-feruloyl-α-L- arabinofuranose and possibly 5-O-feruloyl-α-L-arabinofuranosyl-(1 → 3)-O-β-D-xylopyranose. Their mean content, measured as esterified ferulic acid (FA), was 2.5 times higher in maize (10.33 ± 2.40 μg/g) compared to wheat. Digestion under gastric or pH conditions resulted in a two-fold increase in F-AXOS in all samples. The level of F-AXOS produced during gastric or pH condition was positively correlated to the insoluble bound FA content of the sample (R 2 = 0.98). 5-O-Feruloyl-α-L- arabinofuranose was the only identifiable F-AXOS released during gastric digestion. Our results suggest feruloyl arabinose is the most abundant form of F-AXOS in maize and wheat.